Reproductive Outcome in Female Wistar Rats Following Treatment with Cucurbita pepo (Pumpkin) Seed Extracts - Anyanwu, C. F.; Georgewill, O. A.; Obinna, Victoria C. (British Journal of Healthcare and Medical Research, 2025)
Due to healthcare shortages and high infertility costs, medicinal plants and herbal preparations with fertility properties are gaining popularity in developing countries. In this study, female wistar rats were treated with n-hexane (nHE), dichloromethane (DCM), and aqueous ethanol (Aq. Eth) extracts of Cucurbita pepo seed to investigate its effect onreproductive outcome in female wistar rats. 48 rats were randomly divided into 12 of 4 rats each for daily oral gavage treatment for 21 days: A (control) = 0.5ml 20% tween 80 (vehicle); B (positive control) = 10mg/kg clomiphene citrate; C, D, and E = 142.86, 285.71, and 428.57 mg/kg nHE; F, G, and H = DCM; and I, J, and K = Aq.Eth extracts. Group L (positive control 2): 8 days/10mg/kg clomiphene citrate. After treatment, rats mated 2:1 with males. Mating confirmation day was gestational day 0. On GD 20, animals were laparatomised and reproductive outcome was assessed by foetal weight, FCRL, litter size, implantation, and resorption sites. On reproductive outcome indices, all extracts exhibited no significant effect (p >0.05).Clomiphene citrate markedly reduced reproductive outcome indices. It can be concluded that Cucurbita pepo seed Cucurbita pepo seed had no effect on female rats' reproductive outcomes at the dosages and period utilised in this investigation. These findings can be starting point for further researchto ascertain if variations in duration or doses of Cucurbita pepo seed extracts may yield different outcomes.